JURISDICTION AND COMPETENCE IN CIVIL PROCEEDINGS - Durdona Rixsievna Nazarova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
The precise allocation of adjudicative authority through subject-matter competence and territorial jurisdiction constitutes the structural baseline of functional civil justice. This investigation quantitatively deconstructs the procedural bottlenecks generated by ambiguous jurisdictional boundaries within domestic litigation. Utilizing a stratified empirical legal methodology, the research analyzes 540 civil and commercial disputes characterized by formal jurisdictional challenges adjudicated between 2021 and 2025. Logistic regression modeling reveals that boundary ambiguity in corporate-civil hybrid disputes triggers a 42.6% rate of initial misallocation, causing severe procedural latency averaging 89.4 days before substantive hearings commence. Structural analysis demonstrates a powerful inverse correlation between statutory clarity and the frequency of appellate nullifications (r = -0.76, p < 0.01). The findings dictate an immediate legislative transition toward automated, centralized electronic docketing algorithms designed to definitively resolve initial competence inquiries, optimizing resource allocation and eliminating protracted preliminary litigation.